2022
DOI: 10.3390/vaccines10101630
|View full text |Cite
|
Sign up to set email alerts
|

Glaucoma Cases Following SARS-CoV-2 Vaccination: A VAERS Database Analysis

Abstract: Background: To counter the rapidly spreading severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), global vaccination efforts were initiated in December 2020. We assess the risk of glaucoma following SARS-CoV-2 vaccination and evaluate its onset interval and clinical presentations in patients. Methods: We performed a retrospective analysis of the glaucoma cases reported to the Vaccine Adverse Event Reporting System (VAERS) database between 16 December 2020, and 30 April 2022. We assessed the crude repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In the past, ocular adverse events such as uveitis, keratitis, and optic neuritis have been reported after vaccinations. 9,[16][17][18] Herpetic eye disease is the most common cause of infectious and inflammatory keratitis, primarily caused by HSV and VZV. [19][20][21] The causative viruses typically infect humans during the early years and remain dormant for decades in the neurons of dorsal root ganglia, cranial nerve ganglia, and autonomic ganglia until reactivation due to trauma, stress-related triggers or due to an immune compromised state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, ocular adverse events such as uveitis, keratitis, and optic neuritis have been reported after vaccinations. 9,[16][17][18] Herpetic eye disease is the most common cause of infectious and inflammatory keratitis, primarily caused by HSV and VZV. [19][20][21] The causative viruses typically infect humans during the early years and remain dormant for decades in the neurons of dorsal root ganglia, cranial nerve ganglia, and autonomic ganglia until reactivation due to trauma, stress-related triggers or due to an immune compromised state.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, ocular adverse events such as uveitis, keratitis, and optic neuritis have been reported after vaccinations. 9,16–18…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication [ 28 ] assessed the risk of vaccine-associated uveitis (VAU) following SARS-CoV-2 vaccination using the Centers for Disease Control and Prevention (CDC) Vaccine Adverse Events Reporting System (VAERS). The study found an estimated crude reporting rate (per million doses) of 0.57, 0.44, and 0.35 for BNT162b2, mRNA-1273, and Ad26.COV2.S, respectively, i.e., the three vaccines rarely caused VAU.…”
Section: Discussionmentioning
confidence: 99%
“…Since the commencement of the most extensive global vaccination efforts, few studies have evaluated the safety concern of ophthalmic adverse events following SARS-CoV2 vaccination using the VAERS database. [14][15][16] Here, we assess the cases of VAR following the administration of the three United States Food and Drugs Administration (FDA) authorized COVID-19 vaccines (BNT162b2, mRNA-1273 and Ad26.COV2.S) reported to the VAERS from all over the world. In addition, we evaluate the demographics, association with the type of corneal transplantation, average VAR onset interval post-vaccination and clinical characteristics observed in patients.…”
Section: Clinical Sciencementioning
confidence: 99%